Assessment of physicochemical parameters of groundwater of Oligocene aquifers in Warsaw, Poland as reserves in emergencies - Bralewska, Karolina; Rakowska, Joanna (Journal of Water and Land Development, 2026)
The waters found in the Oligocene formations are widely recognised as an excellent source of high-quality drinking water that does not require pretreatment or disinfection. This study aimed to evaluate the physicochemical properties of groundwater of Oligocene aquifers in Warsaw, Poland, which occur at a depth of 200–300 m, to compare them with drinking water standards, and to determine their suitability for consumption in crisis situations. Water samples were collected from ten randomly selected wells. The parameters assessed included pH, conductivity, temperature, turbidity, water hardness, and the concentrations of the following ions: antimony, arsenic, chromium, cadmium, copper, nickel, aluminium, mercury, lead, fluoride, chloride, ammonium, nitrate, sulphate, sodium, and iron. The average values of all analysed parameters were below the maximum limits established for drinking water. However, chloride ion and iron levels exceeded permissible limits at one and two sampling points, respectively. Nevertheless, analysis of the remaining parameters at these specific measurement points suggests that these elevated levels are not caused by anthropogenic sources. The mean values of most of the parameters (16/19) aligned with the first groundwater quality class, indicating excellent quality. The research conducted indicates that Oligocene water is suitable for human consumption in emergency situations. However, it should be noted that the assessment did not consider the presence of microorganisms. The obtained results emphasise the importance of maintaining and regularly monitoring the quality of existing public water sources. Such measures are essential to ensure that these sources remain a reliable emergency water supply.